Etnomatematika Melalui Simbol dan Komunikasi Nonverbal dalam Tradisi Marosok di Minangkabau - Rani Rahim (Jurnal Ilmiah Universitas Batanghari Jambi, 2023)
Studies that examine mathematical ideas or practices in various cultural activities are known as ethnomathematics. Ethnomathematics studies mathematical ideas in various cultural activities carried out by ethnic, social or professional groups. This research was conducted as part of the exploration in the Marosok trade tradition by the Minangkabau tribe in West Sumatra. This study aims to reveal the practice of mathematics through symbols and gestures contained in buying and selling transactions through the Marosok tradition in Minangkabau. The Marosok buying and selling tradition is the tradition of shaking hands "Marosok" or touching a finger covered with cloth (cover), between the seller and the buyer with the aim of getting an agreement on the price in the sale and purchase of livestock using nonverbal communication. This nonverbal communication activity can be used as a context to support language diversity in mathematics. Language diversity can facilitate all students with diverse learning needs. This research uses qualitative research with literature study method. The results obtained from this study indicate that symbols and finger gestures in the Marosok tradition contain the basic numbers one, two, three, four, five and two and a half as well as two types of operations in mathematics, namely addition and subtraction. These finger symbols and gestures can be used as a math practice.